Imogolite Prepared from Cement Kiln Dust Removes Arsenite from Water - Arancibia-Miranda, N; Arancibia-Miranda, N; Manquian-Cerda, K; Manquian-Cerda, K (Elsevier B.V., 2023)
Imogolite belongs to the family of nanotubular metal oxides which are useful for the construction of new materials in nanotechnology. This study aims to develop a simple waste valorization method to obtain imogolite from cement kiln dust (CKD) via solubilization of CKD and subsequent precipitation of imogolite (Imo-CKD) in a hydrothermal process. The newly synthesized Imo-CKD and a conventional imogolite (Imo) showed similar diameter (Ø) and length (L) of nanotubes [Ø≅ 1.9 nm and L ≅ 200 nm] and crystallinity grade but different values of isoelectric point (IEP) [IEPImo−CKD=8.86 and IEPImo=9.92]. The shift in the IEP value of Imo-CKD to a lower value was attributed to the presence of allophane as a subproduct during Imo-CKD synthesis. Arsenite [As(III)] removal from water by both the imogolites was a rapid (t ≤ 20 min) and spontaneous process. The kinetic As(III) removal data obeyed the pseudo-second order model, while surface diffusion also controlled the As(III) adsorption process. The activation energy (Ea > 40 kJ mol−1) suggested a chemical adsorption of As(III) in both materials. The Imo-CKD (0.377 mmol g−1) removed As(III) from water more efficiently than Imo (0.334 mmol g−1), despite the formation of allophane byproduct in the synthesis process. Results of this study can promote the reuse of inexpensive CKD as a viable alternative to replace costly tetraethyl orthosilicate for imogolite synthesis and use of imogolite for water pollutant removal. © 2023 The Author(s)